Development of lactose hydrolyzed milk using micro fluidization assisted crude β-galactosidase enzyme of Lactobacillus acidophilus - Kaur, Devsimran; Mishra, Santosh Kumar; Singh, Pranav Kumar; N., Veena; Rokana, Namita (Indian Journal of Dairy Science, 2023)
The objectives of this study were to screen maximum β-galactosidase enzyme producing Lactobacillus strain out of seven commercial lactobacilli and development of lactose hydrolyzed milk using micro fluidization assisted crude β-galactosidase enzyme from selected maximum β-galactosidase enzyme producing Lactobacillus strain. From all the screening methods L. acidophilus ATCC 4356 culture was found to possess the maximum β-galactosidase enzyme, so this culture was selected for further studies. Crude β-galactosidase enzyme extract (CEE) was obtained from L. acidophilus ATCC 4356 using micro fluidization as a cell disruption method. A total of 37.41 (µmol/ mL/ min) enzyme activity was obtained from the crude extract. Lactose hydrolysis in milk was done using different concentrations (0.5, 1 and 1.5%) of CEE of L. acidophilus ATCC 4356. CEE@1.5% showed the highest 39.96% hydrolysis of lactose when compared with other CEE-added milk after 8 h. There was a significant difference found when sensory scores were recorded for lactose hydrolyzed milk obtained by using crude enzyme extracts concentrations @1.5% CEE of L. acidophilus ATCC 4356 and 1% commercial enzyme. In conclusion, lactose hydrolyzed milk was successfully developed using crude enzyme extract and being an economical, innovative and therapeutic product, large-scale production of the product can be taken up by large players in the field in future.